Effect of Sacrificial Anodes and Marine Growth on Hydrodynamic Coefficients of Rigid Cylinders - ., VJ Kurian, AM Al-Yacouby, AA Sebastian, MS Liew, VG Idichandy (2015)
Estimation of accurate hydrodynamic coefficients for tubular cylinders fitted with anodes and wrapped with marine growth is a complex task. The interaction of fluid with sacrificial anodes and marine growth surface is not fully understood. The objective of this study is to determine the effect of sacrificial anodes and marine growth on hydrodynamic coefficients of rigid cylinders experimentally. In this study tubular cylinders with outer diameter Do = 42 mm were tested in the wave tank. The total hydrodynamic forces and the corresponding drag and inertia coefficients were analyzed at different Keulegan Carpenter (KC) numbers. The tests were conducted in the offshore engineering laboratory of Universiti Teknologi PETRONAS, Malaysia. In this experimental investigation, a scale factor ʎ of 1:55 was adopted and all the parameters are analyzed and presented in terms of scaled up prototype values in accordance with Froude scaling law. The test results suggest that the cylinder fitted with sacrificial anodes and the one wrapped with rough surface have shown an overall increase in drag and inertia coefficients.